The Potential of Various Cosmetic Preparations of Tomato Fruit (Solanum lycopersicum) in Medicinal Uses: A Systematic Literature Review - Anita Fajriyani; Nurfirzatulloh, Icha; Iin Suherti; Mutiara Insani; Ridha Alisthipa Sephia; Rifka Adya Shafira; Nia Yuniarsih (Eureka Herba Indonesia, 2023)
In the cosmetic field, tomatoes can be processed into various preparations that can be used to maintain and improve skin health. Extracts or other natural ingredients derived from tomatoes can be used in cosmetic products. This study is a systematic review study with the aim of exploring the potential of various tomato cosmetic preparations in improving health. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of various cosmetic preparations of tomato fruit (Solanum lycopersicum) in medicinal uses. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Extracts or other natural ingredients derived from tomatoes can be used in products such as skin-lightening creams, anti-aging face masks, moisturizers, cleansing soaps, and enzyme peels.